Policy framework for utilization and conservation of below-ground biodiversity in Kenya = Estrategias para la utilización y conservación de la biodiversidad del subsuelo en Kenia - Achieng, C; Okoth, Peter F.; Macharia, A; Otor, S (2009)
The reasons for the lack of inclusion of below-ground biodiversity in the Kenyan policy and legal framework were sought. Gaps were identified in the relevant sectoral policies and laws in regard to the domestication of the Convention on Biological Diversity (CBD). Below -ground biodiversity had no specific schedule in any of the sectoral laws. Most sectoral laws were particular about the larger biodiversity and soils but had no mention of belowground biodiversity. Material Transfer Agreements and Material Acquisition Agreements that are regarded as tools of domestication of the CBD to guide transfers, exchanges and acquisition of soil organisms lacked a regulating policy. The lack of regulating policy could be attributed to the delay in approval of draft regulations by the Ministry of Environment while the lack of inclusion of belowground biodiversity in Kenya’s legal and policy framework could be as a result of lack of awareness and appreciation among stakeholders.